Fungal infections in pediatric patients with acute myeloid leukemia in a tertiary hospital - Ávila Montiel, Diana; Saucedo Campos, Alberto; Avilés Robles, Martha; Murillo Maldonado, Marco Antonio; Jiménez Juárez, Rodolfo; Silva Dirzo, Marisol; Dorantes Acosta, Elisa (Frontiers in Public Health, 2023)
Acute leukemia accounts for more than 30% of all pediatric cancer cases, and of these, 15–20% are acute myeloid leukemia (AML). Children who suffer from AML are more likely to develop infections due to the humoral and cellular immune deficits generated by the disease and its treatment. The incidence of fungal infections is underestimated; reports show that up to 75% of fungal infections go undiagnosed until autopsy. In only thirty years, the incidence of invasive candidiasis has increased by 40-fold. Thus, the high morbidity and mortality associated with fungal infections in hematological patients make it necessary to adopt preventive measures. This work aimed to retrospectively identify pediatric patients with acute myeloid leukemia and invasive fungal diseases (IFDs) in a Latin American tertiary care hospital. A retrospective analysis of 36 clinical records of pediatric patients diagnosed with AML from 2007 to 2017 was carried out. One hundred and twenty-nine hospitalizations were associated with infectious events. Thirteen patients in our study presented 15 infectious events associated with IFDs (11.6%). Two patients died because of complications related to IFDs (15.3%). The most frequent IFD type was aspergillosis, which was observed in 7 cases, followed by candidemia, which was observed in 4 cases. The most frequent clinical manifestations were fever and respiratory distress. Mortality due to IFD can be prevented with effective pharmacotherapy. An appropriate antifungal prophylaxis strategy still needs to be developed through larger prospective studies in Latin America.